Accelerated life testing for packaging decisions in the edible oils distribution. (June 2017) - Manzini, Riccardo; Accorsi, Riccardo; Piana, Francesco; Regattieri, Alberto
Graphical abstract: Highlights: In long-ray shipments thermal stress can compromise the performance of packaging. Reliability of a packaging is the ability to respond to stresses throughout the logistic process. Three applications of ALT analysis to food packaging for edible oils are illustrated. Well-known approach of ALTA in the novel application of food packaging prototyping and design. The proposed approach is effective to aid decision-making in the design of robust packaging. Abstract: Food packaging is subjected to environmental stresses during its life cycle. Thermal stresses, which are highly recurrent in long-ray shipments, influence and compromise the expected performance of the package, as well as the quality of the product. This paper illustrates three significant applications of accelerated life testing analysis (ALTA) to food packaging for edible oils, demonstrating the effectiveness of such an approach to aid decision-making in the design of robust packaging solutions. The first and second case studies adopt constant-stress loading and Arrhenius prediction modeling, while the third adopts cyclical stresses and cumulated-damage prediction modeling rarely discussed in the literature. The conducted predictive and comparative analyses demonstrate the effectiveness of ALTA in the novel application of food packaging prototyping and provide guidelines for packaging improvements in response to the experienced transport conditions.